Experimental study and gyrokinetic simulations of isotope effects on core heat transport in JET tokamak deuterium and tritium plasmas - D. Brioschi; P. Mantica; A. Mariani; N. Bonanomi; E. Delabie; J. Garcia; N. Hawkes; I. Jepu; D. Keeling; E. Lerche; E. Litherland-Smith; C.F. Maggi; et al. (Nuclear Fusion)
This paper presents a study on the dependence of the ion temperature stiffness on the plasma main ion isotope mass in JET ITER-like wall and C wall discharges. To this aim, a database of H, D and T shots is analyzed, including new dedicated shots, comparing experiments with lower and higher power injected by the NBI system. In order to characterize the turbulence dependence on the isotope mass, three of these discharges (two in T and one in D) with same external heating scheme are studied in detail and interpreted with gyrokinetic linear and nonlinear simulations. The analysis is performed at fixed radius $ρ_tor = 0.33$ , selected in order to maximize the electromagnetic stabilizing effects on turbulence, both from thermal and suprathermal particles. The experimental results show a clear ion temperature stiffness reduction when heavier isotopes are considered, thus moving from H to D to T, which is attributed to an increasing thermal electromagnetic stabilization with increasing main isotope mass.